INFLUENCE OF MUSIC ON THE AMATEUR TRAINING OF PRACTITIONERS OF SPINNING (Fiep Bulletin - online, 2013)
This research, which is a descriptive bibliographical study of qualitative nature, sought to investigate the influence of the use of the music Spinning classes, both in aspects related to physical performance, on the socioafetivos. The relevance of this work is based on the need for exploration of assumptions that subsidize the practice, as well as the practice of Spinning, as when considering the bibliography on the themes addressed, very few studies were found in the area. So, we decided to first conceptualize the Spinning and various types of training. Then performed the song as an intervening factor which influences the physical activity and, finally, the correlation of music with the performance of the amateur sportsman. It is concluded that this modality, by having the associated music, greatly increases the performance of amateur and professional practitioners of this activity, as well as positively influence on interpersonal relationships, contributing to the reduction of stress and increased self-esteem.
Keywords: physical education; Music; Spinning.